1990
DOI: 10.1002/eji.1830201217
|View full text |Cite
|
Sign up to set email alerts
|

Processing without proteolytic cleavage is required for recognition of insulin by T cells

Abstract: Beef insulin as well as a chymotryptic A-chain fragment [BI-A1-14(SSO3-)3] need uptake by antigen-presenting cells (APC) for efficient presentation in combination with major histocompatibility complex class II molecules to insulin-specific T cells. This could be shown by the inability of aldehyde-fixed APC to present these antigens to T cells. Furthermore, presentation of the insulin fragment as well as presentation of ovalbumin (OVA) was inhibited by treatment of APC with chloroquine, cerulenin or tunicamycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…We emphasize that the data with fixed APC reported by Naquet et al (8) suggest that even the minimal A(1-14)/B (7)(8)(9)(10)(11)(12)(13)(14)(15) peptide requires further processing. Evidence for further processing requirements of sulfonated and disulfide forms of A chain peptides were also provided by Miller et al (12) in studies with human loop-specific T cell clones and those of Gradehandt et al (11,32) using A~bAok-restricted clones. The first demonstration of efficient presentation of insulin peptides by fixed APC is provided by the current study.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…We emphasize that the data with fixed APC reported by Naquet et al (8) suggest that even the minimal A(1-14)/B (7)(8)(9)(10)(11)(12)(13)(14)(15) peptide requires further processing. Evidence for further processing requirements of sulfonated and disulfide forms of A chain peptides were also provided by Miller et al (12) in studies with human loop-specific T cell clones and those of Gradehandt et al (11,32) using A~bAok-restricted clones. The first demonstration of efficient presentation of insulin peptides by fixed APC is provided by the current study.…”
Section: Discussionmentioning
confidence: 80%
“…This conclusion is consistent with the results of Falcioni et al (13), who demonstrated that >90% of a large panel of I-Ab-restricted beef insulin-reactive T cell clones responded to sulfonated A chain but not performic acid-oxidized insulin. Gradehandt et al (11,32) have demonstrated that A~bA~-restricted clones recognize an A (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) determinant that is sensitive to performic acid oxidation. It was proposed that processing of insulin is not dependent on proteolysis, but rather on modification or conversion of disulfide bridges.…”
Section: Discussionmentioning
confidence: 99%
“…the presence or absence of Chq for additional 4 h. Following antigen pulsing they were fixed with 0.05 YO glutaraldehyde (EM grade) for 40 s. The reaction was stopped with L-lysine (0.1 M) [38] …”
Section: Cell Linesmentioning
confidence: 99%
“…A second approach to identifying enzymes involved in Ag processing is to digest Ag with purified proteases in vitro and test for recognition by Th in the presence of fixed APC. Such studies have implicated three different proteases in Ag processing: the aspartyl protease cathepsin D and the cysteine proteases cathepsins B and L [14,15,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%